“Relación entre el examen completo de orina y el urocultivo en el diagnóstico de infecciones urinarias en pacientes del Hospital III José Cayetano Heredia – Piura, en el primer semestre del 2016” - Guerrero Jaime, Paola Adriana (2017)
To determine the relationship between complete urine and urine culture in the diagnosis of urinary tract infections in patients from the Hospital III José Cayetano Heredia - Piura, in the first half of 2016; A direct, retrospective, cross-sectional and comparative observational study was considered; Where a secondary information source consisting of the Hospital Management System database was used, which were processed with statistical models to obtain the results, which explain that of the cases evaluated, 20.14% had a diagnosis of infections Urinary and were reported as positive, and 79.86% did not present a diagnosis of urinary tract infections and were reported as negative, suggesting that there are more positive cases in female patients and is evidenced by the presence of more than 50 Leukocytes by microscopic field, the presence of abundant piocitos and bacteria; It is concluded that there is a direct relationship between the parameters of the urine and urine tests in the diagnosis of urinary tract infections. At the same time, the presence of leukocytes, piocitos, bacteria and nitrites is indicative of urinary infection; Therefore, the application of the urine culture is necessary.